PILLARS OF COASTAL COMMUNITY RESILIENCE DALAM MENGHADAPI BENCANA BANJIR ROB DI KOTA SEMARANG - Gandisa Pangestuti Kiswoyo; Hartuti Purnaweni; Rizki Hidayati; Nilam Adini Rakhma (Universitas Diponegoro, 2026)
The city of Semarang is a coastal urban area in Indonesia facing increasingly complex flood risks each year. This phenomenon is caused by rainfall, land subsidence, and climate change, which have led to increased social, economic, and environmental vulnerability among coastal communities. This study aims to analyze the resilience of coastal communities in facing flood disasters by examining the five main pillars of resilience: governance, risk assessment, knowledge and education, risk management and vulnerability reduction, as well as disaster preparedness, response, and recovery. This study employs a qualitative approach using a case study method, analyzed through thematic analysis to identify patterns, interconnections among the pillars, and the dynamics between policies and practices at the community level. The findings indicate that the resilience of coastal communities in Semarang tends to be dominated by reactive and incremental adaptation, rather than transformational capacity. Furthermore, there is a mismatch between government structural interventions and community adaptation practices, indicating that top-down approaches have not yet been integrated with local capacities. Additionally, this study identifies the phenomenon of false resilience a strategy to endure recurring disasters that actually masks vulnerabilities and normalizes risk as part of daily life. This study contributes to the field of resilience and coastal governance by employing a resilience-pillar-based analytical framework, while also offering a critical examination of the context of urban coastal areas. The findings underscore the importance of a more adaptive, participatory, and context-specific approach to disaster management in building sustainable resilience.